International Students’ Experience and the Effect of Satisfaction on Brand Loyalty in Malaysia Public Higher Education: A Conceptual Framework - Azemi, Helmie Sheha Che; Romle, Abd Rahim (South Asian Journal of Social Sciences and Humanities, 2021)
Service experience appears to be essential in a variety of academic disciplines. In business management, the service experience is a touchstone that impacts on profit, customer satisfaction, and loyalty. However, service experience has been pretty much ignored in higher education. With the intense competition between institutions, university management needs to create new enthusiasm and strategy for managing students’ experience, especially foreign students. This study proposed a conceptual framework to examine the relationship between students’ experience with brand loyalty, which is mediated by satisfaction. The research design will employ a quantitative approach using a structural equation model to obtain the result.
Keywords: Students’ experience; satisfaction; brand loyalty; higher education; conceptual